„Pornograficzne” interpretacje klasycznych mitów w starożytności grecko-rzymskiej - Wypustek, Andrzej (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The paper deals with the phenomenon of “pornographic”, obscene interpretations of mythology in the Greco–Roman era. To date, this subject has remained largely neglected, despite the long tradition of mythological research, the contemporary fashion for study of ancient eroticism and sexuality, and the great role they played in Greek and Roman mythology. It is likely that the traditions of this kind, due to their nature, have disappeared almost without a trace. The author conducts a preliminary review of the preserved, fragmentary evidence, which has not yet been examined together: Pompeian graffiti mentioning a sexual interpretation of the myth of the fight of Heracles and Geryon, epigrams from the Palatine Anthology, Roman literature and historiography, Christian literature, paintings from Pompeii and Herculaneum and elsewhere, representations on Roman pottery, gems, lamps and mirrors.